Unlocking the power of population health management to strengthen primary health care - José Cerezo-Cerezo; Esteban de Manuel-Keenoy; Daniel Alton; Marc Bruijnzeels; Arnoldas Jurgutis; Melitta Jakab (Atención Primaria)
Population health management (PHM) is a people-centred, data-driven and proactive approach to improving the health and well-being of a defined population, considering the differences within that population and their social determinants of health. By using quantitative and qualitative data insights, PHM helps primary care providers identify population cohorts with similar needs or ‘at risk’ of a given negative outcome/s. This enables primary care providers to address their needs in a targeted, tailored, proactive and holistic way through coordination with other care levels and sectors. PHM can be summarized conceptually in a cycle of five steps: defining and identifying the population; health assessment and segmentation; risk stratification and impactibility; tailored service delivery; and evaluation and improvement. The relationship between primary health care (PHC) and PHM is that of a virtuous circle. PHM helps make PHC more effective and many elements of a strong PHC-oriented model of care are essential for effective PHM. Resumen: La gestión poblacional de la salud (GPS) es un enfoque proactivo, centrado en las personas y basado en los datos para mejorar la salud y el bienestar de una población determinada, teniendo en cuenta las diferencias dentro de esa población y sus determinantes sociales de la salud. Mediante el uso de datos cuantitativos y cualitativos, la GPS ayuda a los proveedores de atención primaria a identificar cohortes de población con necesidades similares o «en riesgo» de un/os determinado/s resultado/s negativo/s. Esto permite a los proveedores de atención primaria abordar sus necesidades de forma específica, adaptada, proactiva y holística mediante la coordinación con otros niveles y sectores asistenciales. La GPS puede resumirse conceptualmente en un ciclo de cinco pasos: definición e identificación de la población; análisis de la salud y segmentación de la población; estratificación de la población e impactabilidad; prestación de servicios adaptada, y evaluación y mejora. La relación entre la atención primaria de salud (APS) y la GPS es la de un círculo virtuoso. La GPS contribuye a hacer la APS más eficaz, y muchos elementos de un modelo de atención orientado a la APS son esenciales para la GPS.